On Browsing - Bankapur, M. B. (Journal of Information and Knowledge, 1988)
Inspite of the "Electronic Technological Revolution" in the field of information processing system, the role of conventional modes of information systems present themselves as a covetable success scored through the diffussion and utilization of information. Browsing forming part of the search process, serves as an art, as a reflection of an experience, pushing through the user toward a direct link that is not thought about and not analysed. Browsing established the intellectual precision a distinctiveness in the respective context of a rational enquiry. The study envisages the unique characteristics of browsing techniques and points out direct involvement of the user, sustaining the use of surrogative systems of the library and of its collection. It is asserted that interface and browsing are synonymous except a few technical observations. Browsing creates an environment of enlightenment.